Stable carbon isotope stratigraphy of the Silurian in the Jočionys-299 borehole (eastern Lithuania) - Tomas Želvys; Antanas Brazauskas; Andrej Spiridonov; Mykolas Balčiūnas; Andrius Garbaras; Sigitas Radzevičius (Estonian Journal of Earth Sciences, 2022)
In recent years it has become commonplace to formalize chemostratigraphic units and identify isotopic zones (chemoÂstratigraphic units) from excursions. Stable carbon isotopes have been used in solving stratigraphic problems in the Silurian for more than 30 years. Î´13C data supplement other stratigraphic proxies, allowing the subdivision of geological sections and more precise correlation. In this paper we give new Î´13C data from the Silurian section of the JoÄionys-299 borehole, which is located in eastern Lithuania, crossing shallow marine and lagunal deposits. Based on Î´13C variability, the Ireviken carbon isotope excursion (CIE), the Å lilalÄ CIE, and probably the Valgu CIE have been identified in the investigated section. The Valgu CIE is linked to the lower part of the Å venÄionys Formation. The Ireviken CIE is linked to the upper parts of the Å venÄionys Formation and the Paprieniai Formation (rise in Î´13C values), the JoÄionys Formation (moderately stable Î´13Ccarb values) and the VerknÄ Formation (fall in Î´13C values). A small negative Î´13C shift is documented in the PabradÄ Formation. Chemostratigraphy together with biostratigraphic data allow us to correlate eastern Lithuanian lithostratigraphic units (shallow marine environment) with the global Silurian Geochronological Scale more accurately.